2021
DOI: 10.1140/epjd/s10053-021-00291-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of static and dynamic femtosecond laser modifications of Ti/Zr multilayer thin films

Abstract: The experimental study of the static and dynamic femtosecond laser ablation of the multilayer 15x(Ti/Zr)/Si system is reported. The layer-by-layer selective laser ablation mechanism was studied by analysis of the surface morphology and elemental composition in static single pulse irradiation in a range of pulse energy from 10 to 17 $$\upmu $$ μ J. The selective ablations, as number of concentric circles in modified spots are increased with the pulse energy. The boundary be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…The results indicate that oxygen from the atmosphere more readily oxidized the surface where copper was present. Taking into account the current and previous studies of a similar Ti/Zr multilayer system, it can be concluded that a larger fraction of the laser pulse energy delivered to the system induces intense ablation (removal of between 100 and 200 nm thin film), while a smaller fraction of the absorbed energy induces changes in the composition, coinciding with a change in the lattice temperature (in-depth about 50 nm) based on the numerical simulation of the temperature profile [36,46,47]. Surface free energy (SFE) can be considered a quantity that characterizes the affinity of a surface for other materials (e.g., liquids).…”
Section: Resultsmentioning
confidence: 95%
“…The results indicate that oxygen from the atmosphere more readily oxidized the surface where copper was present. Taking into account the current and previous studies of a similar Ti/Zr multilayer system, it can be concluded that a larger fraction of the laser pulse energy delivered to the system induces intense ablation (removal of between 100 and 200 nm thin film), while a smaller fraction of the absorbed energy induces changes in the composition, coinciding with a change in the lattice temperature (in-depth about 50 nm) based on the numerical simulation of the temperature profile [36,46,47]. Surface free energy (SFE) can be considered a quantity that characterizes the affinity of a surface for other materials (e.g., liquids).…”
Section: Resultsmentioning
confidence: 95%